2018
DOI: 10.3389/fgene.2018.00043
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Novel LAMA2 Mutations in a Chinese Patient with Congenital Muscular Dystrophy

Abstract: Merosin-deficient CMD type 1A (MDC1A), caused by mutations of laminin subunit alpha 2 (LAMA2), is a predominant subtype of congenital muscular dystrophy (CMD). Herein, we described a Chinese patient with MDC1A who was admitted to hospital 17 days after birth because of marasmus and feeding difficulties. Mutations were identified by targeted capture and next generation sequencing (NGS) and further confirmed by Sanger sequencing. Paternity was confirmed by short tandem repeat analysis. Physical examination showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…The majority of reported genetic variations of MDC1A are homozygous or compound heterozygous variants (6,7). De novo variations in contrast are not common events and only a few have been reported in patients with MDC1A (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of reported genetic variations of MDC1A are homozygous or compound heterozygous variants (6,7). De novo variations in contrast are not common events and only a few have been reported in patients with MDC1A (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 10 Moreover, de novo mutations are the rare events and a few have been reported in MDC1A patients. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…The early diagnosis of MDC1A is based on high serum concentrations of CK, deficiency of merosin in skin or muscle biopsy, alterations in white matter on brain, and clinical examination. 11 Previous studies reported the efficiency of whole‐exome sequencing (WES) for the molecular diagnosis of the congenital muscular dystrophy. 13 , 14 However, use of WES method is not cost‐effective in patients with clinical overlap.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis of LAMA2 -related muscular dystrophy is based on clinical findings, elevated serum creatine kinase, abnormal white matter signal on T2-weighted MRI, complete or partial laminin α2 subunit on IHC staining of muscle, and biallelic mutation of the LAMA2 gene [ 18 ]. Molecular diagnosis of LAMA2 -related muscular dystrophy provides the advantage of avoiding invasive muscle biopsy [ 19 , 20 ] and allows determination of the inheritance pattern. DNA testing is performed for other family members when the mutation in the proband is known.…”
Section: Introductionmentioning
confidence: 99%